2013
DOI: 10.1111/roiw.12089
|View full text |Cite
|
Sign up to set email alerts
|

Distributional Characteristics of Income Insecurity in the U.S., Germany, and Britain

Abstract: This paper studies income volatility using recent data from the Cross National Equivalence File (CNEF). Measures of downward instability are applied to household income streams and the results are interpreted as indicators of income insecurity. Using this method we examine (i) cross national differences in average insecurity levels, (ii) the effects of taxes and transfers, and (iii) relationships between the insecurity index and household income. Insecurity estimates based on pre-government incomes are highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…The industry dummies continue to imply that there is a lower degree of insecurity for individuals belonging to well‐defined industrial groups, a similar result to that reported by Rohde et al . (). Notably, this was especially strong in industries that employed high‐skilled workers.…”
Section: Covariates Of Insecurity Indicesmentioning
confidence: 97%
“…The industry dummies continue to imply that there is a lower degree of insecurity for individuals belonging to well‐defined industrial groups, a similar result to that reported by Rohde et al . (). Notably, this was especially strong in industries that employed high‐skilled workers.…”
Section: Covariates Of Insecurity Indicesmentioning
confidence: 97%
“…However the concept can be operationalized by measuring specific phenomena that are likely to be stressful and combining these indicators with the aim of inferring the resultant sense of anxiety. Economic insecurity is thus seen as a multidimensional concept that includes (alongside job insecurity) the risk of poverty (Bandyopadhyay & Cowell, 2007;Calvo & Dercon, 2005), income volatility Smith, Stoddard & Barnes, 2011;Rohde, Tang & Rao, 2014), bankruptcy (Kalleberg, 2009), loss through family dissolution, crime or widowhood (Western, Bloom, Sosnaud & Tach 2013;Osberg & Sharpe, 2002), wealth dynamics (Bossert & D'Ambrosio, 2013;D'Ambrosio & Rohde, 2014) and lack of access to insurance, in particular health insurance (Dominitz & Manksi, 1997;Bucks, 2011;Hacker, 2006;Hacker et al, 2010). At the aggregate level phenomena such as business cycles (Stuckler et al, 2011) and exposure to international competition (Scheve & Slaughter, 2004;Standing, 1997) are also relevant.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Income based indicators typically measure negative instability and have been used as a basis for measurement by Hacker et al (2010), Rohde et al (2014) and Nichols and Rehm (2014). The central idea is that volatility, and in particular downward movements, will highlight an unreliable income and therefore capture an important aspect of insecurity.…”
Section: Income Stream Indicatorsmentioning
confidence: 99%
“…For instance, Barnes and Smith (2011) consider different proxies for economic insecurity: individuals' unemployment probability using information from the last five years, individuals' probability of experiencing an income loss pushing them beneath the poverty threshold (considering a 16-year, de-trended household annual income) and the number of annual real income drops exceeding 10%. Rhode, Tang, and Rao (2014), instead, use 15 years of income information and identify individuals in households whose relative income shares over time have had a negative trend as economically insecure.…”
Section: Income Mobility and Economic Insecuritymentioning
confidence: 99%
“…In this vein, we use income instability in a two-year period to measure the dimension of economic insecurity and to identify the covariates that make an individual most exposed to it. Obviously, similarly to Rhode et al (2014), we take a narrow definition of insecurity because we have restricted our analysis to income volatility or mobility as a determinant of insecurity, while ignoring other sources of risk and the heterogeneous capacity of individuals to cover this risk through the use of previous wealth. 4 However, we are endogenously taking into account the role of two crucial sources of individual income stabilization and protection against risk: the dimension and effectiveness of the tax and transfer systems and the household's demographic structure.…”
Section: Income Mobility and Economic Insecuritymentioning
confidence: 99%